Second language learning produces vowel mispronunciation in the pupils of seventh grade in Domingo Savio School, for boys - Salas Gallegos, Manuel Mesías (2007)
It is acknowledged that the native language not only affects the ability to produce English sounds but also the ability to hear English sounds. Thus, in Ecuador where the majority of people speak Kichwa and or Spanish, teachers of English from Napo noticed that Kichwa speaking students have better pronunciation than Spanish speaking students, in this context the Province of Napo has two education departments, one education department is bilingual Kichwa and Spanish and, the another education department is Spanish only. Spanish Department includes English in the time-table and in the rural area it usually does not exist in primary in the schedule due to staff shortages. Students are continually frustrated when they produce new communication in this case when the sound is incorrect they repeat a mispronounced word, without clear knowledge. We noticed young children practices the sounds of the Spanish language they are learning they imitate, repeat, and sign consonant and vowel combination without effort. It is considered that learning to speak another language in this case English must be natural and automatic too, I consider, it is vital to teach and improve the speech in beginners learning of American English as a foreign language. Thus, it was written with the general EFL population in mind but it should be especially have to keep in mind use of the Multiple Intelligences, the Direct Method, the Suggestopedia Method, the Silent Method, the Community Language Learning Method, the Total Physical Response Method, the Communicative Approach for those pupils who wish to communicate more clearly in familiar, and academic, settings. Thus, vowel pronunciation is identified as a major problem of learning another language. We noticed some pupils can read, write and understand American English, but the majority will face situations in which their pronunciation interferes with clear and effective communication. Nowadays, English is not only the first language of business, sport and entertainment, but also is a worldwi spoken language included in the educational curriculum as a subject or even as a way of instruction necessary to get job, access to higher education, travel, etc, thus, important for pupils to improve their vowel pronunciation so they will be able to communicate confidently and be understood with relative ease.